2010
DOI: 10.1584/jpestics.g09-63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokinin on production of diterpenoid phytoalexins in rice

Abstract: IntroductionHigher plants that are attacked by pathogenic microorganisms respond with a variety of defense reactions, including the production of secondary metabolites called phytoalexins, which serve as plant antibiotics.In rice, 15 compounds have been identified as phytoalexins in suspension-cultured cells treated with a biotic elicitor such as a chitin oligosaccharide or a cerebroside [1][2] and/or in leaves either infected with the blast fungus Magnaporthe oryzae or irradiated with UV light. [3][4][5][6][7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Thus, while SA may not be essential for cytokinin-induced immunity in early defence responses such as scopoletin and capsidiol biosynthesis, it certainly contributes to the overall defence response. In agreement with this, a synergistic action of cytokinins and SA was found to regulate the production of another type of phytoalexin, known as diterpenoid phytoalexins, during defence responses of rice to M. oryzae (Ko et al, 2010;Akagi et al, 2014), and this response is dependent on both SA and the SA signalling regulator WRKY45 (Akagi et al, 2014).…”
Section: If I Don't Fight There Will Be Trouble: Cytokinins In Plant-mentioning
confidence: 75%
“…Thus, while SA may not be essential for cytokinin-induced immunity in early defence responses such as scopoletin and capsidiol biosynthesis, it certainly contributes to the overall defence response. In agreement with this, a synergistic action of cytokinins and SA was found to regulate the production of another type of phytoalexin, known as diterpenoid phytoalexins, during defence responses of rice to M. oryzae (Ko et al, 2010;Akagi et al, 2014), and this response is dependent on both SA and the SA signalling regulator WRKY45 (Akagi et al, 2014).…”
Section: If I Don't Fight There Will Be Trouble: Cytokinins In Plant-mentioning
confidence: 75%
“…CK was reported to induce the expression of DP biosynthetic genes and the accumulation of their products in rice (Ko et al 2010). Recently, we showed that the synthetic CK kinetin acts synergistically with the SA signaling pathway to induce PR gene expression in rice (Jiang et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Jasmonates, ET and salicylic acid (SA) are the hormones whose interactive roles in defense signaling are most often considered, but almost all phytohormones, including abscisic acid, auxins, cytokinins, brassinosteroids and GAs, have been shown to influence monocot responses to biotic attack (De Vleesschauwer et al, 2013). Similar to jasmonates, exogenous application of natural and synthetic cytokinins to rice cells and leaf disks induced accumulation of diterpenoid phytoalexins and transcripts encoding the respective biosynthetic enzymes (Ko et al, 2010). During M. oryzae infection, increased levels of endogenous cytokinins are also detectable, together with transcription of cytokinin-responsive genes sharing the OsRR6 (response regulator 6) promoter (Jiang et al, 2013).…”
Section: Involvement Of Phytohormonesmentioning
confidence: 99%